2015
DOI: 10.1007/978-1-4939-2522-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Studying ER Stress and UPR Markers in Human Cells

Abstract: Many experimentally induced or disease-related cellular dysfunctions stress the endoplasmic reticulum, commonly resulting in an accumulation of unfolded proteins in the ER lumen which is sensed by three ER-resident transmembrane proteins, PERK, ATF6, and IRE1. Their activation by such ER stress affects the unfolded protein response, which consists of a shutoff of protein translation and at the same time the switching-on of specific transcription factors that control genes which function to reduce the burden of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 12 publications
1
30
0
2
Order By: Relevance
“…As shown in Figure 1A-E, TG treatment rapidly induced potent upregulation of GRP78, ATF4, CHOP, XBP1s and ATF6. Since the expression of ER stress-related genes is used as a marker of ER stress (Dey et al, 2010;Kennedy et al, 2015;Namba et al, 2007), these results indicate a successful induction of ER stress in our experimental condition. Associated with the increase of ER stress, mRNAs of CXCL10 and CCL2 were robustly increased in a time-dependent manner and reached peak expression at 3 to 6 hours after TG treatment ( Figure 1F and 1G).…”
Section: Endoplasmic Reticulum (Er) Stress Induces Cxcl10 and Ccl2 Prsupporting
confidence: 59%
“…As shown in Figure 1A-E, TG treatment rapidly induced potent upregulation of GRP78, ATF4, CHOP, XBP1s and ATF6. Since the expression of ER stress-related genes is used as a marker of ER stress (Dey et al, 2010;Kennedy et al, 2015;Namba et al, 2007), these results indicate a successful induction of ER stress in our experimental condition. Associated with the increase of ER stress, mRNAs of CXCL10 and CCL2 were robustly increased in a time-dependent manner and reached peak expression at 3 to 6 hours after TG treatment ( Figure 1F and 1G).…”
Section: Endoplasmic Reticulum (Er) Stress Induces Cxcl10 and Ccl2 Prsupporting
confidence: 59%
“…In several cell lines, ER stress has been found to be activated following UA exposure [37-39] and was reported to be involved in UA-induced apoptosis in one of these studies [39]. The results of the present study revealed that high levels of UA induced ER stress in cultured cardiomyocytes as well as rat myocardium, as evidenced by the increased GRP78, p-PERK, and CHOP expression, which are widely used as markers of ER stress [40-43]. …”
Section: Discussionmentioning
confidence: 55%
“…A previous study has suggested that the IRE1 pathway is involved in the ER stress response (15). The RNase activity of IRE1α is activated following ER stress and its spliced form may reflect the activation of IRE1α (16).…”
Section: Involvement Of the Ire1 Pathway With Tsa Treatmentmentioning
confidence: 93%